Efektivitas Eksperimen Sederhana “Gunung Meletus’’ Untuk Meningkatkan Minat Belajar Dan Sikap Sains Anak Di Tk Nu Al-Madani - Anggun; Suci Ahirotunisa Ahirotunisa; Hidayatu Munawaroh (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
Literally science can be called the science that studies events that occur in nature. Meanwhile, conceptually science is defined as a conceptual scheme that is related to each other by a series of experiments and observations and can be tested further. Science for early childhood is science whose target is aimed at early childhood and how to understand science from a child's perspective. Currently, it is important to introduce science to young children. This is because science can encourage children to think critically, and with science, children do not simply accept or reject something. Educating children to have scientific abilities can help parents and children to actively build self-defense against information attacks from around them. Science games are science learning activities that are fun and familiar to children, so that children actively look for solutions. Providing science learning from an early age can train children to use their thoughts, strength and honesty so that children are ready to move towards a higher level of education. The aim of this research is to determine the effectiveness of the volcano eruption game in increasing students' interest in learning about science. Research activities or scientific discoveries where children can understand their world through simple observations, investigations and experiments. This research was conducted at the NU AL-MADANI Kindergarten. The research method used is classroom action research, which is a type of classroom action research that aims to explore educators' actions in implementing an experimental approach in science learning for early childhood. Data collection in this research uses several techniques, namely observation is used to collect data about students' activity levels during the learning process and experimental methods. The experiment carried out was a simple volcano eruption experiment using simple ingredients, namely baking soda, food coloring, vinegar and sand. The results of research on the influence of experimental methods in growing the scientific competence of group A children at the Nu Al-Madani Ngabean Kindergarten, show that children's scientific competence can increase through volcanic eruption experimental activities when children observe all the tools and materials, as well as the process in the volcanic eruption experimental activity.